Electronic structure of Mo1−xRex alloys studied through resonant photoemission spectroscopy. (14th June 2016) - Sundar, Shyam; Banik, Soma; Sharath Chandra, L S; Chattopadhyay, M K; Ganguli, Tapas; Lodha, G S; Pandey, Sudhir K; Phase, D M; Roy, S B
Abstract: We studied the electronic structure of Mo-rich Mo1− x Re x alloys ( 0 ⩽ x ⩽ 0.4 ) using valence band photoemission spectroscopy in the photon energy range 23–70 eV and density of states calculations. Comparison of the photoemission spectra with the density of states calculations suggests that, with respect to the Fermi level E F, the d states lie mostly in the binding energy range 0 to  −6 eV, whereas s states lie in the binding energy range  −4 to  −10 eV. We observed two resonances in the photoemission spectra of each sample, one at about 35 eV photon energy and the other at about 45 eV photon energy. Our analysis suggests that the resonance at 35 eV photon energy is related to the Mo 4 p –5 s transition and the resonance at 45 eV photon energy is related to the contribution from both the Mo 4 p –4 d transition (threshold: 42 eV) and the Re 5 p –5 d transition (threshold: 46 eV). In the constant initial state plot, the resonance at 35 eV incident photon energy for binding energy features in the range E F ( BE   =  0) to  −5 eV becomes progressively less prominent with increasing Re concentration x and vanishes for x   >  0.2. The difference plots obtained by subtracting the valence band photoemission spectrum of Mo from that of Mo1− x Re x alloys, measured at 47 eV photon energy, reveal that the Re d -like states appear near E F when Re is alloyed with Mo. These results indicate that interband s – d interaction, which is weak in Mo, increases with increasing x and influences the nature of the superconductivity in alloys with higher x .